The relationship between different ventricular rate control levels and cardiac remodeling in early persistent atrial fibrillation: a prospective cohort study - Liu, Yongrong; Liu, Jun; Wang, Dan (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAtrial fibrillation (AF) is a prevalent cardiac arrhythmia, with ventricular rate control being a critical therapeutic target. However, the optimal range for ventricular rate control remains unclear. Additionally, the relationship between different levels of ventricular rate control and cardiac remodeling in patients with atrial fibrillation remains unclear.ObjectiveThis study aims to explore the relationship between different levels of heart rate control and cardiac remodeling in patients with early persistent atrial fibrillation.MethodsA bi-center prospective cohort study was conducted, enrolling patients with newly diagnosed persistent AF and rapid ventricular rates, yet with a normal cardiac size, from March 2019–May 2020 at the people's hospital of Chongqing Hechuan and the First Affiliated Hospital of Zhengzhou University. Patients were divided into four groups based on their average ventricular rate levels from 24 h Holter monitoring: Group I (40 ≤ average rate < 60 bpm), Group II (60 ≤ average rate <80 bpm), Group III (80 ≤ average rate < 100 bpm), and Group IV (average rate ≥ 100 bpm).The study tracked changes in left atrial diameter (LAD), left ventricular end-diastolic diameter(LVEDD),left ventricular ejection fraction(LVEF), and the severity of mitral regurgitation over one year.ResultsA total of 764 patients were enrolled. We found that there were no significant differences in cardiac remodeling among the groups of patients before the observation. However, after one-year follow-up observation, there were significant differences in the degree of cardiac remodeling among the groups (p < 0.001). Specifically, the severity of cardiac remodeling, including LVEDD, LAD, LVEF, and mitral regurgitation, showed the following trend: Group II < Group I < Group III < Group IV. Further regression analysis indicated that body mass index (BMI) might be related to changes in LAD. Additionally, the use of digoxin could affect changes in left ventricular ejection fraction. At the same time, the use of diltiazem, bisoprolol, as well as factors like hypertension, coronary artery disease, smoking, diabetes, and chronic obstructive pulmonary disease, might be closely associated with the worsening of mitral regurgitation.ConclusionThis study shows that in early persistent AF patients, different levels of heart rate control are related to varying degrees of cardiac remodeling. These results suggest that maintaining an average ventricular rate within the range of 60–80 beats per minute may be associated with milder cardiac remodeling. On the other hand, an average heart rate greater than 100 bpm appears to be associated with the most severe cardiac remodeling.Registration NumberChiCTR2400079978; Registered 17 January 2024–Retrospectively registered: https://www.chictr.org.cn/showproj.html?proj=198684.